2017
DOI: 10.3389/fnagi.2017.00363
|View full text |Cite
|
Sign up to set email alerts
|

Distinct Aging Effects on Motion Repulsion and Surround Suppression in Humans

Abstract: Elderly exhibit accumulating deficits in visual motion perception, which is critical for humans to interact with their environment. Previous studies have suggested that aging generally reduces neuronal inhibition in the visual system. Here, we investigated how aging affects the local intra-cortical inhibition using a motion direction discrimination task based on the motion repulsion phenomenon. Motion repulsion refers to the phenomenon by which observers overestimate the perceived angle when two superimposed d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
11
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 55 publications
1
11
0
Order By: Relevance
“…We found that spatial suppression decreased with age in healthy controls-an effect consistently found in previous studies (Betts et al 2005;Betts, Sekuler, and Bennett 2009;Yazdani et al 2015;Zhuang et al 2017;Pitchaimuthu et al 2017;Tadin et al 2019;Deng et al 2017;Karas and McKendrick 2012) . Here, we found that this age-mediated perceptual alteration also occurs in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 89%
“…We found that spatial suppression decreased with age in healthy controls-an effect consistently found in previous studies (Betts et al 2005;Betts, Sekuler, and Bennett 2009;Yazdani et al 2015;Zhuang et al 2017;Pitchaimuthu et al 2017;Tadin et al 2019;Deng et al 2017;Karas and McKendrick 2012) . Here, we found that this age-mediated perceptual alteration also occurs in patients with schizophrenia.…”
Section: Discussionsupporting
confidence: 89%
“…Meanwhile, it is widely accepted that our brain is highly adaptive and flexible in processing and interpreting the incoming visual information (e.g., see Deng, Chen, Kuang, & Zhang, ; Di Luca, Ernst, & Backus, ; Haijiang, Saunders, Stone, & Backus, ; Kaliuzhna, Prsa, Gale, Lee, & Blanke, ; Kuang & Zhang, ). The same work of art is differentially perceived and appreciated by artists and nonartists who have little artistic training.…”
mentioning
confidence: 99%
“…The cortical connectivity deficit is also compatible with a previous finding showing a decline in volume in many white matter regions of the AD brain (Kuang, ; Salat et al ., ). In a wider perspective, dysfunctions of cortical connections, especially those inhibitory micro‐circuit, are linked to perceptual and cognitive impairments identified in ageing (Betts, Taylor, Sekuler, & Bennett, ; Deng, Chen, Kuang, & Zhang, ) and several neurological disorders including AD and schizophrenia (Anticevic et al ., ; Festa et al ., ; Kuang, , ).…”
Section: Discussionmentioning
confidence: 99%